2022
DOI: 10.1016/j.envres.2021.112624
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the responses of highly time-resolved PM2.5 related elements to extreme emission reductions

Abstract: China's unprecedented lockdown to contain the spread of the novel coronavirus disease (COVID-19) in early 2020, provided a tragic natural experiment to investigate the responses of atmospheric pollution to emission reduction at regional scale. Primarily driven by primary emissions, particulate trace elements is vitally important due to their disproportionally adverse impacts on human health and ecosystem. Here 14 trace elements in PM 2.5 were selected for continuous measurement hourly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…These results are in line with other works that have shown significant reductions in PM 2.5 primary components concentrations (e.g. K, Fe, Zn, Ba, Mn, Pb, Cu, As, Ni, Se and Cr, in Cheng et al (2022) ; Cr, Fe, Na + , Cl − , Pb, Ca, Cr, Cu, Fe, Zn and EC, in Li et al (2021) ; Zn, Pb, Mn, As, Cu, Ni, V, Cr, Cd and Co, in Wang et al (2021b) ; Cd, Se, As, Sr, Ba, Cu, Mn, Pb, K, Zn, Ca, Al, and Mg, in Nguyen et al (2022) ), attributed as an effect of the measures imposed by the COVID-19 lockdown. Soil elements Al and Si, did not vary significantly, since being of natural origin, were less affected by the reduction of anthropogenic activities.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in line with other works that have shown significant reductions in PM 2.5 primary components concentrations (e.g. K, Fe, Zn, Ba, Mn, Pb, Cu, As, Ni, Se and Cr, in Cheng et al (2022) ; Cr, Fe, Na + , Cl − , Pb, Ca, Cr, Cu, Fe, Zn and EC, in Li et al (2021) ; Zn, Pb, Mn, As, Cu, Ni, V, Cr, Cd and Co, in Wang et al (2021b) ; Cd, Se, As, Sr, Ba, Cu, Mn, Pb, K, Zn, Ca, Al, and Mg, in Nguyen et al (2022) ), attributed as an effect of the measures imposed by the COVID-19 lockdown. Soil elements Al and Si, did not vary significantly, since being of natural origin, were less affected by the reduction of anthropogenic activities.…”
Section: Resultssupporting
confidence: 93%
“…Globally, these results are in line with other works, where PMF source apportionment generally revealed decreased contributions of vehicle emissions ( Cui et al, 2020 ; Cheng et al, 2022 ; Wang et al, 2021a ) and in some cases, also increased contributions of secondary inorganic aerosol ( Chang et al, 2022 ; Hong et al, 2021 ; Massimi et al, 2022 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In 2020, the meteorological data of Shanghai during the lockdown period and before and after the lockdown were consistent. The comparison of 14 trace elements in PM 2.5 found that the concentration of trace elements in most fine particles showed a “V” shape trend, indicating that the lockdown measures had a significant impact [ 34 ]. Comparing the air quality index (AQI) results before and after the impact of COVID-19 across India shows that most pollutant concentrations (PM 10 , PM 2.5 , CO, SO 2 , NO x ) show different patterns of gradual to rapid decreases [ 35 , 36 ].…”
Section: Results Of the Metrological Analysismentioning
confidence: 99%
“…PM 2.5 -bound elements have long been considered trace components (“trace elements”) and are mainly used to infer particulate sources. Recently, in addition to toxicological studies, there has been increasing interest in linking human health risks with PM 2.5 -bound element measurements to inform mitigation policies. This is particularly true in China, where haze pollution featuring high PM 2.5 loadings continued to be a severe environmental and health concern in North China Plain, the Yangtze River Delta region, and the Pearl River Delta region . For example, Huang et al characterized the concentration and fractionation of 14 elements in Beijing and concluded that traffic-related emission dominated the carcinogenic risk (CR) and noncarcinogenic risk (NCR) by PM 2.5 -bound elements during low pollution days, while coal combustion becomes equally or even more important during moderate and severe pollution days.…”
Section: Introductionmentioning
confidence: 99%